2020
DOI: 10.1002/rsa.20947
|View full text |Cite
|
Sign up to set email alerts
|

Weighted distances in scale‐free preferential attachment models

Abstract: We study three preferential attachment models where the parameters are such that the asymptotic degree distribution has infinite variance. Every edge is equipped with a nonnegative i.i.d. weight. We study the weighted distance between two vertices chosen uniformly at random, the typical weighted distance, and the number of edges on this path, the typical hopcount. We prove that there are precisely two universality classes of weight distributions, called the explosive and conservative class. In the explosive cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…First-passage percolation. In view of the above discussion, we recall the static counterpart of Theorem 1.1 by the authors in [37] that generalizes earlier results on graph distances in PAMs [15,21,25]. In [37,Theorem 2.8] it is shown that, for weight distributions satisfying…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…First-passage percolation. In view of the above discussion, we recall the static counterpart of Theorem 1.1 by the authors in [37] that generalizes earlier results on graph distances in PAMs [15,21,25]. In [37,Theorem 2.8] it is shown that, for weight distributions satisfying…”
Section: Introductionmentioning
confidence: 65%
“…Now we prove the lower bound of Theorem 1.1, i.e., we show that with probability close to one there is no too short path between u t and v t for any t ≥ t. The main contribution of this section versus existing literature, e.g. [15,21,37], is the following proposition concerning the graph distance. In its proof we develop a path-decomposition technique that uses the dynamical construction of PA t in a refined way to get strong error bounds that are summable over t ≥ t. After the notational and conceptual set-up of the argument, we state and prove some technical lemmas.…”
Section: Proof Of the Lower Boundmentioning
confidence: 74%
See 3 more Smart Citations